Carryover effects of winter mercury contamination on summer concentrations and reproductive performance in little auks. (1st February 2023) - Carravieri, Alice; Lorioux, Sophie; Angelier, Frédéric; Chastel, Olivier; Albert, Céline; Bråthen, Vegard Sandøy; Brisson-Curadeau, Émile; Clairbaux, Manon; Delord, Karine; Giraudeau, Mathieu; Perret, Samuel; Poupart, Timothée; et al.
Abstract: Many animals migrate after reproduction to respond to seasonal environmental changes. Environmental conditions experienced on non-breeding sites can have carryover effects on fitness. Exposure to harmful chemicals can vary widely between breeding and non-breeding grounds, but its carryover effects are poorly studied. Mercury (Hg) contamination is a major concern in the Arctic. Here, we quantified winter Hg contamination and its carryover effects in the most abundant Arctic seabird, the little auk Alle alle . Winter Hg contamination of birds from an East Greenland population was inferred from head feather concentrations. Birds tracked with Global Location Sensors (GLS, N = 28 of the total 92) spent the winter in western and central North Atlantic waters and had increasing head feather Hg concentrations with increasing longitude ( i.e., eastward). This spatial pattern was not predicted by environmental variables such as bathymetry, sea-surface temperature or productivity, and needs further investigation. Hg concentrations in head feathers and blood were strongly correlated, suggesting a carryover effect of adult winter contamination on the consequent summer concentrations. Head feather Hg concentrations had no clear association with telomere length, a robust fitness indicator. In contrast, carryover negative effects were detected on chick health, as parental Hg contamination in winter was associated with decreasing growth rate of chicks in summer. Head feather Hg concentrations of females were not associated with egg membrane Hg concentrations, or with egg volume. In addition, parental winter Hg contamination was not related to Hg burdens in chicks' body feathers. Therefore, we hypothesise that the association between parental winter Hg exposure and the growth of their chick results from an Hg-related decrease in parental care, and needs further empirical evidence. Our results stress the need of considering parental contamination on non-breeding sites to understand Hg trans-generational effects in migrating seabirds, even at low concentrations. Graphical abstract: Image 1 Highlights: Winter Hg contamination and its carryover effects were quantified in little auks. Winter Hg contamination increased eastward in the North Atlantic Ocean. Blood Hg contamination in summer was predicted by winter Hg exposure. Winter Hg contamination had no clear effect on telomere length or body condition. Parental winter Hg burdens were negatively associated with chick growth.